Ankle-brachial index – effective diagnosis of peripheral arterial disease - Cierzniakowska, Katarzyna; Szewczyk, Maria T.; Kozłowska, Elżbieta; Mościcka, Paulina; Górka, Anna; Popow, Aleksandra; Cwajda-Białasik, Justyna (Pielęgniarstwo Chirurgiczne i Angiologiczne/Surgical and Vascular Nursing, 2016)
Objectives: Diagnosis based on evaluation of blood pressure ratio measured around the ankle to the highest systolic arm pressure is known as ankle-brachial index (ABI). Reduced blood pressure around the ankle in relation to the blood pressure around the arm indicates the presence of peripheral arterial disease. The aim of this study was the assessment of ABI and co-ocurrance of artherosclerosis risk factors among tested people. Material and methods: The tested group consisted of 128 people (45 women and 83 men) aged from 50 to 93. This group included 64 patients with diagnosed peripheral arterial disease. The study was conducted using own questionnaire. After the research, all tested people had ABI measured for both legs. Results : Average ABI values were as follows: for diabetic people 0.47 ±0.38 (p = 0.006); for smokers 0.51 ±0.39 (p = 0.00045); for people with limited physical activity 0.49 ±0.38 (p = 0.0001) for underweight people 0.13 ±0.18 and for people with correct weight 44 ±0.36 (p = 0.007). Significant differences concerned also the parameters based on the self-assessment of the patients (material status and health status). More than a half of patients (53%) with peripheral arterial disease limits their activity. In terms of physical activity there are significant intergroup differences (p = 0.02). Conclusions : Significantly lower ABI among patients was determined be chosen parameters like: diabetes, smoking, little physical activity, lower BMI. Patients with PAD have significantly worse assessment of their own health, material status and physical activity in comparison to the rest of groups.